Determian Harga Sukuk Korporasi - Azhar, Arya Aditya; Dailibas, Dailibas (Peneliti.net, 2023)
The purpose of this study was to determine the effect of Profitability and Solvability on Corporate Sukuk Prices simultaneously or partially for the 2017-2021 period. This research took samples using the purposive sampling method from 6 companies. The data in this study is secondary data and collected by the method of documentation from the Indonesia Bond Market Directory and the annual reports of each company. Data were analyzed using multiple linear regression methods to find the relationship between profitability and solvency on Sukuk prices. The results of this study are profitability and solvency simultaneously have a significant effect on Sukuk prices. Partially, profitability has a positive and insignificant effect on the price of sukuk, while solvency has a negative and significant effect on the price of sukuk. Recommendations for investors to pay attention to the company's solvency before buying the sukuk.